Wind Power Generator for Small Scale Fish Processing Unit at Coastal Area in Aceh, Indonesia - . Hamdani; . Irwansyah (Syiah Kuala University, 2012)
This paper presents a wind power technology used to generate electricity forsmall scale fish processing unit. The units consist of ice machines, green house solar dryer, fish smoke house and utilities. A 10 kW wind turbine system were installed in 2010 at Lancang Paru village, Pidie Jaya. Total number of energy required for small scale fish processing unit are calculated. Initial test shown that wind power generator able to produce maximum power of 5 kW at 4 m/s wind speed. This wind turbine is enough to provide electricity for small scale fish processing unit